Analisis Leverage dan Profitabilitas Terhadap Nilai Perusahaan (Studi Pada Pt. Bank Panin Dubai Syariah Periode 2016-2020) - Wilyandi, Wilyandi; Arisandi, Debby; Wahyuni, Eka Sri (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2023)
This research analysis the effect of leverage and profitability on firm value at PT Bank Panin Dubai Syariah for the 2016-2020 period. The main purpose of establishing a company is to maximize shareholder wealth. There are several factors that affect firm value, for example leverage and profitability. This study uses a quantitative approach with time series analysis. Thei results of this study indicate that leverage and profitability have no effect on firm value, while the simultaneous significance test shows that leverage and profitability have an effect on firm value. This means that companies in financing their assets tend to use their own capital (internal financing) which comes from retained earnings and share capital rather than using debt.